Developing English for Tourism and Hospitality Materials based on Banyuwangi Local Needs - Nurhalimah Nurhalimah; Reni Nur Jannah (JURNAL SOSIAL HUMANIORA (JSH), 2022)
The Ministry of Education and Culture stepped up the connect-and-match effort by creating a teaching factory to combine vocational education with the industrial world. The program's goal is to increase the number of graduates from vocational schools who are employed as trained and qualified human resources (HR) to meet the demands of the sector. The suitability and relevance of the material to local needs, especially in the world of tourism in Banyuwangi should be included in the learning materials. In order to establish a link and match, it is required to conduct a thorough examination of the development of learning instruments. The purpose of this study is to develop English for Tourism and Hospitality teaching materials in accordance with the local needs of the tourism industry in Banyuwangi. This research was an R & D (Research and Development) using the ADDIE model. The results showed that the English for Tourism and Hospitality materials that would be applied to the Tourism Business Management Study Program, Banyuwangi State Polytechnic were relatively varied and diverse which was divided into two parts, namely materials that reflect the Banyuwangi local culture such as Gedhogan, Kemiren, Gandrung Sewu, Barong Kemiren, Seblang Dance, Ngopi Sepuluh Ewu, Ijen Blue Fire, Tumpeng Sewu Festival, Red Island, as well as additional materials related to hospitality such as Hotel, Restaurant, and Travel Agent.